Digital Marketing Activities at IDEMU by Vivere - Silvanus Alvin; Angela Yasmin (Jurnal Ekonomi dan Bisnis Digital, 2023)
Digital marketing is a strategy that utilizes digital media to connect both potential customers and companies. One of the companies engaged in furniture that implements digital marketing is IDEMU by Vivere. This research was conducted with the main objective of finding out the digital marketing activities carried out by IDEMU. This research includes qualitative research with a case study method. The interesting finding of this research is that IDEMU's digital marketing focuses on Instagram and collaboration with influencers. Furthermore, collaboration with influencers is more inclined than collaboration with microinfluencers because the target customer is more niche.